Pengaruh Kualitas Layanan dan Brand Trust terhadap Loyalitas Pelanggan pada Café Hill&Tiff Palopo - Marsal Marsal; Muh. Fadhli Febrian; Alda Azzahra; Agung Syahputra; Jusrianti Malino (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of service quality and brand trust on customer loyalty at Café Hill & Tiff in Palopo City. A quantitative approach was employed, with data collected through questionnaires distributed to 35 respondents who are customers of the café. The data were analyzed using multiple linear regression to examine both simultaneous and partial effects between variables. The results show that service quality and brand trust simultaneously have a significant influence on customer loyalty, with a significance value of 0.011 (< 0.05) and an F-value of 5.365 (> F-table 3.35). Partially, both variables also have a positive and significant impact. The coefficient of determination (R²) indicates that 28.4% of the variation in customer loyalty can be explained by service quality and brand trust, while the remaining 71.6% is influenced by other factors outside this study. These findings underscore the importance of consistently delivering quality service and building brand trust as strategic efforts to maintain customer loyalty amid increasing business competition.